Tinjauan fiqih aqad dalam jual beli online - Prista, Alexchandra Nurfadila (Maliki Interdisciplinary Journal, 2023)
In the economy, it is inseparable from the sale and purchase contract. Where the contract itself is an agreement between two parties, the seller and the buyer. In the fiqh contract, all buying and selling activities must be avoided from usury, gharar which can harm one of the parties and eliminate the pleasure of the perpetrator of the contract. Even now it is very vulnerable to happen because of the convenience of today’s technology. As with buying and selling online where it is very likely for fraud to occur which can harm certain parties. With the ease of buying and selling contracts, there will be an increasing number of enthusiasts to buy and sell online, where not everything is in accordance with the Shari’a. Where the seller only gives a description of the goods and the buyer only knows the characteristics of the object being purchased without seeing directly the item to be purchased. This research is used to find out what might happen in online buying and selling contracts that are not in accordance with Shari’a. Like the sale and purchase contract with the concept of khiyar and the sale and purchase contract that occurs because of things that damage the contract.